Exploring implementation and sustainability of models of care: can theory help? - Forster Della A; Newton Michelle; McLachlan Helen L; Willis Karen (BMC Public Health, 2011)
Abstract Objective Research on new models of care in health service provision is complex, as is the introduction and embedding of such models, and positive research findings are only one factor in whether a new model of care will be implemented. In order to understand why this is the case, research design must not only take account of proposed changes in the clinical encounter, but the organisational context that must sustain and normalise any changed practices. We use two case studies where new models of maternity care were implemented and evaluated via randomised controlled trials (RCTs) to discuss how (or whether) the use of theory might inform implementation and sustainability strategies. The Normalisation Process Model is proposed as a suitable theoretical framework, and a comparison made using the two case studies – one where a theoretical framework was used, the other where it was not. Context and approach In the maternity sector there is considerable debate about which model of care provides the best outcomes for women, while being sustainable in the organisational setting. We explore why a model of maternity care – team midwifery (where women have a small group of midwives providing their care) – that was implemented and tested in an RCT was not continued after the RCT’s conclusion, despite showing the same or better outcomes for women in the intervention group compared with women allocated to usual care. We then discuss the conceptualisation and rationale leading to the use of the ‘Normalisation Process Model' as an aid to exploring aspects of implementation of a caseload midwifery model (where women are allocated a primary midwife for their care) that has recently been evaluated by RCT. Discussion We demonstrate how the Normalisation Process Model was applied in planning of the evaluation phases of the RCT as a means of exploring the implementation of the caseload model of care. We argue that a theoretical understanding of issues related to implementation and sustainability can make a valuable contribution when researching complex interventions in complex settings such as hospitals. Conclusion and implications Application of a theoretical model in the research of a complex intervention enables a greater understanding of the organisational context into which new models of care are introduced and identification of factors that promote or challenge implementation of these models of care.